Treatment With a Growth Factor–Protein Mixture Inhibits Formation of Mineralized Nodules in Osteogenic Cell Cultures Grown on Titanium - de Oliva, Marcos Andrade (Histochemical Society, 2009)
Despite wide clinical application, the efficacy of platelet-rich plasma (PRP) for repairing bone defects and enhancing osseointegration of metal implants is still subject of debate. This study aimed to evaluate the effects of a well-defined PRP-like mixture containing platelet-derived growth factor-BB, transforming growth factor (TGF)-β1, TGF-β2, albumin, fibronectin, and thrombospondin [growth factors (GFs) + proteins] on the development of the osteogenic phenotype on titanium (Ti) in vitro. Human alveolar bone-derived osteoblastic cells were subcultured on Ti discs and exposed during the first 7 days to osteogenic medium supplemented with GFs + proteins and to osteogenic medium alone thereafter up to 14 days. Control cultures were exposed to only osteogenic medium. Dose–response experiments were carried out using rat primary calvarial cells exposed to GFs + proteins and 1:10 or 1:100 dilutions of the mixture. Treated human-derived cell cultures exhibited a significantly higher number of cycling cells at days 1 and 4 and of total cells at days 4 and 7, significantly reduced alkaline phosphatase (ALP) activity at days 4, 7, and 10, and no Alizarin red–stained areas (calcium deposits) at day 14, indicating an impairment in osteoblast differentiation. Although the 1:10 and 1:100 dilutions of the mixture restored the proliferative activity of rat-derived osteogenic cells to control levels and promoted a significant increase in ALP activity at day 10 compared with GFs + proteins, mineralized nodule formation was only observed with the 1:100 dilution (∼50% of the control). These results showed that a PRP-like protein mixture inhibits development of the osteogenic phenotype in both human and rat osteoblastic cell cultures grown on Ti. (J Histochem Cytochem 57:265–276, 2009)